Using Data Mining Technology In Higher Education System - Delavari, Naeimeh (2007)
This research study is designed to present and justify the capabilities of data mining in the context of the higher learning institutions. The main idea in this study is that the hidden patterns that are discovered through data mining techniques cab help managers of higher learning institutions to improve their decision-making processes.